Evaluation of thermocycling, color stability, surface roughness and hardness of nanocarbon HPP, BioHPP and PEEK used for fabrication of prosthetic restorations ( in vitro study) - Mohamed Z. Basiony; Rim A. Selima; Nermeen A. Rady; Sherif M. Abdel Hamid (BMC Oral Health, 2026)
Abstract Statement of problem The selection of appropriate dental materials plays a crucial role in the success of prosthetic restorations. With the limitations of metallic alloys, including their aesthetic shortcomings, weight, corrosion potential, and cost, there is growing interest in high-performance polymer alternatives. Purpose The objective of the present study was to evaluate color stability, surface roughness and Hardness of BioHPP, Nanocarbon HPP and PEEK used for fabrication of prosthetic restorations (An In Vitro Study). Material and methods A total of 42 cylindrical samples (14 per group) were divided into three groups: Group 1: nanocarbon High-Performance Polymer, Group 2: BioHPP, Group 3: PEEK. They were fabricated using CAD/CAM technology and subjected to thermocyclic aging. Color stability was assessed spectrophotometrically after immersion in a staining medium over 28 days. Surface roughness was measured using a profilometer, while hardness was evaluated using the Vickers hardness test. Results Statistically significant differences were observed among all three materials in color stability, surface roughness, and hardness ( p < 0.001). PEEK demonstrated the highest surface roughness, while nano-carbon reinforced polymersexhibited the lowest surface roughness and highest hardness values. In terms of color stability, all materials showed varying degrees of discoloration over time, but nano-carbon-HPP generally maintained better stability. Conclusion Nano-carbon-HPP demonstrated superior mechanical performance, combining low surface roughness with high hardness, making them a promising alternative to traditional materials for full-arch dental prostheses. These findings highlight the potential of nano-carbon materials to improve durability, patient comfort, and aesthetic outcomes in prosthodontic applications. Clinical implication The use of nano‑carbon reinforced polymers may improve the longevity, esthetics, and patient comfort of implant‑supported overdentures.